Post-play communication of emotions facilitates prosociality and cooperation - Gately, J. Braxton; Alsharawy, Abdelaziz (Frontiers in Behavioral Economics, 2024)
Social decisions with monetary consequences are often accompanied with emotional consequences. Previous studies document a robust role of pre-play message communication in facilitating pro-sociality and cooperation. Yet, the effects of communicating emotional experiences in social interactions (particularly post-play) remain understudied. Here, we examine the value of a social environment where emotional expressions are shared post-play in contrast to a private environment where emotion exposure is absent. We develop an experimental design that facilitates emotion exposure and can be readily administered in or outside the laboratory. In this pre-registered online study, participants (N = 196) completed incentivized extensions of the Dictator Game (DG) and the Prisoners' Dilemma Game (PD). Participants learned to classify their emotional experiences on the arousal, valence, and dominance dimensions using non-verbal pictorial representations. Our experiment comprised both a within-subject and a between-subject manipulation: each participant completed a control condition (C, no emotional exposure) as well as an emotion exposure condition (Emotions), but the type of exposure varied between subjects (certain exposure, or Emotions-E, or probabilistic exposure, or Emotions-P). In all conditions, participants complete a one-shot DG and PD. We find that emotion exposure increases other-regarding behavior under both Emotions-E and Emotion-P conditions in the DG and under Emotions-E only in PD. Further, we find that demand for emotion exposure is hardly driven by the outcome of the social interaction (or the actions selected). We also document how empathic concern influence other-regarding behavior and how reports of emotional experiences vary across treatments and with the different outcomes of social interactions. Our results highlight the integral role of emotion exposure in social decision making. Environments that facilitate the communication of emotional experiences increase pro-sociality and encourage cooperation.